Aplikasi Sistem Penunjang Keputusan Pemilihan Konsentrasi Jurusan Pada Program Studi XYZ Dengan Metode Promethee - Lalu Delsi Samsumar; Bahtiar Imran; Salman; Zaenudin (Ikatan Ahli Informatika Indonesia, 2021)
the choice of majoring concentration is something that must be done by every student in the study program when entering Semester 5, where in the XYZ study program at private universities there are three concentration options, namely multimedia, network and RPL. So far, the selection of majors concentration is still inefficient because it does not have a strong basis for consideration when choosing the concentration of majors, there are even some students who prefer to change majors, the cause is that the majors that have been chosen are not in accordance with their abilities and have difficulty in following the lecture material. core. To identify the problems faced by students in choosing the concentration of majors, the promethee approach is used. One of the multivariate decision-making/optimization techniques used in policy analysis, in order to obtain solutions or results from the best alternative majors to be recommended to students. The purpose of this research is to build a web-based DSS application in the Selection of Major Concentrations in the Study Program so that it can assist students in choosing the concentration of majors. The results showed that the ranking of promethee I was based on the value of leaving flow and entry flow (Partial Ranking) while promethee II was based on the value of net flow (Complete Ranking). The application accuracy rate is 70%, this test is carried out by comparing the original data of students who have chosen the concentration of majors with the results of calculations on the system. Of the 30 students who were processed using the promethee SPK, only 21 students were declared in accordance with the original data from the concentration of the majors, this happened because of the lack of consideration of students when choosing the concentration of majors.